Drebrin Regulates Neuroblast Migration in the Postnatal Mammalian Brain - Sonego, Martina; Oberoi, Michelle; Stoddart, Jake; Gajendra, Sangeetha; Hendricusdottir, Rita; Oozeer, Fazal; Worth, Daniel C.; Hobbs, Carl; Eickholt, Britta J.; Gordon-Weeks, Phillip R.; Doherty, Patrick; Lalli, Giovanna (PLOS ONE, 2015)
After birth, stem cells in the subventricular zone (SVZ) generate neuroblasts that migrate along the rostral migratory stream (RMS) to become interneurons in the olfactory bulb (OB). This migration is crucial for the proper integration of newborn neurons in a pre-existing synaptic network and is believed to play a key role in infant human brain development. Many regulators of neuroblast migration have been identified; however, still very little is known about the intracellular molecular mechanisms controlling this process. Here, we have investigated the function of drebrin, an actin-binding protein highly expressed in the RMS of the postnatal mammalian brain. Neuroblast migration was monitored both in culture and in brain slices obtained from electroporated mice by time-lapse spinning disk confocal microscopy. Depletion of drebrin using distinct RNAi approaches in early postnatal mice affects neuroblast morphology and impairs neuroblast migration and orientation in vitro and in vivo. Overexpression of drebrin also impairs migration along the RMS and affects the distribution of neuroblasts at their final destination, the OB. Drebrin phosphorylation on Ser142 by Cyclin-dependent kinase 5 (Cdk5) has been recently shown to regulate F-actin-microtubule coupling in neuronal growth cones. We also investigated the functional significance of this phosphorylation in RMS neuroblasts using in vivo postnatal electroporation of phosphomimetic (S142D) or non-phosphorylatable (S142A) drebrin in the SVZ of mouse pups. Preventing or mimicking phosphorylation of S142 in vivo caused similar effects on neuroblast dynamics, leading to aberrant neuroblast branching. We conclude that drebrin is necessary for efficient migration of SVZ-derived neuroblasts and propose that regulated phosphorylation of drebrin on S142 maintains leading process stability for polarized migration along the RMS, thus ensuring proper neurogenesis.